Implementation of technical and tactical actions qualified athletes in football different roles in gaming areas of the field - Karpa, I.Y. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The aim of the study is to establish the structure of the technical and tactical actions skilled players with a specific game role and areas of the field. Found that the improvement of the technical and tactical actions must be due to functional responsibilities of the players depending on the game role and the different areas of the playing field. Found that the most involved areas on average during the match falls on the linebackers, and the lowest - in the forwards. The last defenders and midfielders mainly perform the technical and tactical actions in the flanking regions, and the central axis of the players - in the central areas of the field. The obtained data confirmed that modern football is important players perform functional duties in accordance with their roles and areas of the field. Differentiated approach is recommended in the process of improving the technical and tactical training of players.